Effect of anterior chest wall myofascial release on thoracic expansion in children with spastic cerebral palsy - Diwan, Shraddha J.; Bansal, Ankita B.; Chovatiya, Hetal; Kotak, Dhara; Vyas, Neeta (International Journal of Contemporary Pediatrics, 2017)
Background: Cerebral Palsy is primarily disorder of development of movement and posture attributed to damage to fetal brain. Children with spastic cerebral palsy are found with decreased chest mobility. Myofascial Release (MFR) is a form of soft tissue therapy used to treat somatic dysfunction and accompanying pain and restriction of motion. Hence some intervention is required to improve chest expansion. So this study was conducted in an effort to improve the chest expansion using MFR techniques to the respiratory muscles. Methods: 12 spastic cerebral palsy children of both genders satisfying inclusion criteria were included for the study. The chest measurements were taken at three levels at axilla, 3 fingers below xiphoid process, and subcostally. These readings were documented as pre-test score. Myofascial release was given to the pectoralis major, intercostals, rectus abdominis and the diaphragm, with the subject in supine position. Post treatment data was taken and statistical analysis was performed. Results: The difference of the pre and post readings of the expansion at the axilla, xiphoid and subcostal shows a mean difference of 0.15, 0.15, 0.20 respectively which is significant statistically, P value being <0.05. Conclusion: The result shows that the chest expansion increased significantly at all the three levels. The expansion improved maximally at the nipple level.